Congenital solitary functioning kidney: evaluations to do which, when, and how - Hyun Kyung Lee (Korean Society of Pediatric Nephrology, 2024)
Congenital solitary functioning kidney (CSFK) is characterized by an anatomical or functional absence of one kidney from birth. When suspected on perinatal ultrasonography (US), repeat US after birth should be performed for confirmation. Although postnatal 99mTc-dimercaptosuccinic acid scintigraphy (DMSA scan) is the gold standard for confirming CSFK, it carries the risk of radiation exposure; US alone is sufficient when performed by an experienced radiologist. One-third of patients with CSFK have additional congenital anomalies of the kidney and urinary tract at the solitary functioning kidney, the most common of which is vesicoureteral reflux. As evidence regarding vesicoureteral reflux with normal kidney US is correlated with significant urinary tract infection is lacking, voiding cystourethrogram may be considered in patients with CSFK with abnormal US findings. Furthermore, approximately 30% of patients with CSFK have extrarenal malformations. Moreover, up to 10% of them have syndromic features. In particular, examining for female genitalia malformations, which can have potential for complications from untreated obstructive malformations, is important. In conclusion, DMSA scan and voiding cystourethrogram are not necessary for all patients with CSFK, and the risk of each patient should be assessed to determine which test is needed during follow-up. The presence of extrarenal manifestations should also always be considered.